The role of labour broker networks in setting the price of working abroad for thai migrant workers - Dusadee Ayuwat; Thanapauge Chamaratana (Asia-Pacific Population Journal, 2014)
The objective of this research was to study the role of labour broker networks in fixing the price for Thai migrants to work abroad. In order to understand the role of these networks, it was necessary to focus on two specific research questions. The first question was how these labour broker networks are formed; and the second question was why, or for what purposes, are these networks being created. Data was collected through in-depth interviews as well as participatory and non-participatory observations with 37 key informants who were labour brokers belonging to legal labour agencies and labour sub-brokers. Key informants were selected by a snowball technique from Udon Thani, Nakhon Ratchasima, Khon Kaen, Chaiyaphum, and Nongkhai. Data analysis was done using the ATLAS.ti program. The study found that the labour broker networks in the north-east of Thailand are loosely established through ties formed via cultural or community activities without any formal organization. In the main, these networks are set up on the basis of personal relationships among members. The rationale behind the establishment of these networks is to maintain personal relationships and to exchange work-related information. The results of the study indicated that the social networks of labour brokers are informal, and that these networks are linked to other networks that exist among labour brokers and sub-brokers forming larger local and regional networks. The costs incurred by Thai migrant workers having recall to the services of labour broker networks forms part of the overall cost of working abroad. Moreover, it was found that in some cases labour sub-brokers had provided loans to Thai labourers to cover the costs of travelling abroad.